Comparison of the exposure of the distal tibial articular surface for posterior pilon fractures via a medial or lateral malleolar osteotomy: a preliminary cadaveric study - Yang, Fan; Ye, Lin; Chen, Cheng; Huang, Moran; Sun, Yihao; Shen, Zhijun; Hu, Jian; Wang, Lei (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to preliminarily investigate the exposure area of the distal tibial articular surface via a medial malleolar osteotomy or transfibular osteotomy and provide a quantitative reference for selecting a surgical approach.MethodsFive pairs of adult fresh-frozen lower extremities were included in the study, and the left and right limbs in each pair were divided randomly into either the medial approach group or the posterolateral approach group. According to the computed tomography scan, a 3D-printed guiding plate was applied to assist in the osteotomy on each specimen. The exposure area of the distal tibial articular surface was calculated after the osteotomy.ResultsThe average ratio of the exposed distal tibial joint dome area to the total distal tibial joint dome area for the medial and posterolateral approaches was 45.94% ± 12.79% and 47.12% ± 12.84%, respectively (S1). Moreover, intra-operative electrocautery marking (S2) yielded 62.72% ± 18.67% and 53.26% ± 10.51%, respectively. When the articular surface was subdivided into the anterior, middle, and posterior thirds, the posterior third demonstrated the greatest exposure (medial 61.3% ± 2.2%; lateral 65.2% ± 1.8%). The inter-observer intraclass correlation coefficient for S1 and S2 exceeded 0.89 (95% CI 0.81–0.97). After maximal soft tissue distraction, the exposed area further increased by 11.5 ± 2.1% (medial) and 9.1 ± 1.6% (lateral), with no significant between-group difference (P = 0.08, paired t-test).ConclusionThe medial and lateral approaches can significantly expose the distal articular surface of the posterior tibia to a large extent after medial and lateral malleolus osteotomies. A suitable individualized surgical approach conducive to adequate exposure for the operation should be considered according to the position of the main fracture fragments on the posterior articular surface and the proportion of their transverse distance to the posterior pilon variant fracture. These preliminary data require clinical validation. In addition, an intra-operative soft tissue stretch enlarges the visual field by approximately 10% regardless of the approach.